2018
DOI: 10.3233/xst-180403
|View full text |Cite
|
Sign up to set email alerts
|

Preliminary clinical application of integrated 125I seeds stents in the therapy of malignant lower biliary tract obstruction

Abstract: The study indicates that integrated 125I seed stents are effective in reducing jaundice symptoms, inhibiting tumor growth, improving stent patency and prolonging patient survival, which may serve as a safer and more feasible method in treating malignant lower biliary obstruction with minimal invasiveness.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
27
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(27 citation statements)
references
References 32 publications
0
27
0
Order By: Relevance
“…Secondly, patients who underwent percutaneous puncture operations were at higher risk. Thirdly, due to operator experience and skills limitations, only interstitial brachytherapy was performed in some centers [13,21,22]. However, intracavitary radiotherapy was feasible due to its minimally invasive technology and ease of manipulation [23].…”
Section: Discussionmentioning
confidence: 99%
“…Secondly, patients who underwent percutaneous puncture operations were at higher risk. Thirdly, due to operator experience and skills limitations, only interstitial brachytherapy was performed in some centers [13,21,22]. However, intracavitary radiotherapy was feasible due to its minimally invasive technology and ease of manipulation [23].…”
Section: Discussionmentioning
confidence: 99%
“…The PRISMA flow diagram for the selection process is presented in Figure 1 . The initial database search yielded 244 potentially relevant studies, ten of which were included in this meta-analysis[ 13 - 15 , 20 - 26 ]. Of these studies, four were retrospective cohort studies and six were RCTs published between 2012 and 2018[ 13 , 14 , 20 , 21 , 25 , 26 ].…”
Section: Resultsmentioning
confidence: 99%
“…The initial database search yielded 244 potentially relevant studies, ten of which were included in this meta-analysis[ 13 - 15 , 20 - 26 ]. Of these studies, four were retrospective cohort studies and six were RCTs published between 2012 and 2018[ 13 , 14 , 20 , 21 , 25 , 26 ]. Five of these RCTs were single-center studies, while one was a multicenter study performed at 20 centers in China[ 21 ].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Compared with external irradiation, brachytherapy delivers a higher effective therapeutic dose to carcinomas and a limited dose to adjacent normal organs and tissues (31). Several studies have demonstrated that 125 I brachytherapy combined with stents achieves technical success, and this approach represents an effective therapy in MOJ patients, manifesting as extended stent patency time, better malignancy control, and consequently prolonged survival (8,9,32,33). Consistent with these studies, our results showed that the median survival was 169 days, and the median stent patency was 120 days.…”
Section: Discussionmentioning
confidence: 99%